2004
DOI: 10.1007/s10875-004-6244-3
|View full text |Cite
|
Sign up to set email alerts
|

CPG 7909, an Immunostimulatory TLR9 Agonist Oligodeoxynucleotide, as Adjuvant to Engerix-B� HBV Vaccine in Healthy Adults: A Double-Blind Phase I/II Study

Abstract: Oligodeoxynucleotides containing immunostimulatory CpG motifs (CpG ODN) act as potent Th1-like immune enhancers with many antigens in animal models. We have extended these observations to the first clinical evaluation of the safety, tolerability and immunogenicity of CPG 7909 when added to a commercial HBV vaccine. In a randomized, double-blind phase I dose escalation study, healthy volunteers aged 18-35 years were vaccinated at 0, 4 and 24 weeks by intramuscular injection with Engerix-B (GlaxoSmithKline). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(222 citation statements)
references
References 23 publications
9
207
1
4
Order By: Relevance
“…Currently, early studies using immunostimulatory CpG oligodeoxynucleotides (CpG ODN) suggest a breakthrough in hepatitis B prevention. Not only do vaccines develop considerably higher titers after three vaccinations with this new combination vaccine, but most of them already mount protective titers after the first vaccination compared to none of the controls immunized with HBsAg alone [37] . It will be interesting to study whether the seroconversion after HBV-CpG ODN vaccination is also accompanied by the induction of T cell responses as shown here and whether previous non-responders will now mount comparable T cell responses as a result of vaccination.…”
Section: Weihrauch Mr Et Al T-cell Response In Hepatitis Bs Non-respmentioning
confidence: 89%
“…Currently, early studies using immunostimulatory CpG oligodeoxynucleotides (CpG ODN) suggest a breakthrough in hepatitis B prevention. Not only do vaccines develop considerably higher titers after three vaccinations with this new combination vaccine, but most of them already mount protective titers after the first vaccination compared to none of the controls immunized with HBsAg alone [37] . It will be interesting to study whether the seroconversion after HBV-CpG ODN vaccination is also accompanied by the induction of T cell responses as shown here and whether previous non-responders will now mount comparable T cell responses as a result of vaccination.…”
Section: Weihrauch Mr Et Al T-cell Response In Hepatitis Bs Non-respmentioning
confidence: 89%
“…The majority of individuals receiving CPG 7909 also developed protective levels of anti-HBs IgG within just 2 weeks of the priming vaccine dose, compared with none of the subjects receiving the commercial vaccine alone. 221 The use of CpG ODN also increased the proportion of antigen-specific high-avidity antibodies, indicating augmentation of the late-affinity maturation in the activated plasmocytes. 222 It is pertinent to note in this context that CpG oligodeoxynucleotides are distinguished in their ability to expand the long-lived memory B cell populations.…”
Section: Intracellular Ssrna Sensing By Rig-i-like Receptors (Rlrs)mentioning
confidence: 95%
“…Furthermore, no signs of systemic toxicity were observed after single or repeated administrations of the malaria candidate vaccines formulated with AS01 or AS02 Adjuvant Systems in rabbits (Segal et al ., 2015). CpG ODNs have been tested as adjuvants in a number of non‐clinical and phase I–III clinical trials testing vaccines against infectious diseases (Cooper et al ., 2004a,2004b; Klinman et al ., 2006; Mullen et al ., 2008) and cancer (Brody et al ., 2010; Pilon‐Thomas et al ., 2006; Speiser et al ., 2005; Valmori et al ., 2007). In previous studies in non‐human primates or in humans, no significant toxicities were reported after injections of CpG 7909 even at high doses (Krieg et al ., 2004; Stewart et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%